Using FDFD Technique in Two-Dimensional TE Analysis for Modeling Clutter in Wall Penetrating Radar - David Insana; Carey M. Rappaport (International Journal of Antennas and Propagation)
Finite difference frequency domain (FDFD) computational electromagnetic modeling is implemented to perform a two-dimensional TEz analysis for the application of wall penetrating radar (WPR). Resolving small targets of interest, embedded in a strong clutter environment of unknown configuration, is difficult. Field interaction between clutter elements will dominate the received fields back-scattered from the scene. Removing the effects of clutter ultimately relies on the accuracy of the model. Analysis starts with a simple model that continues to build based on the dominant scattering features of the scene. FDFD provides a steady state frequency response to a discrete excitation. Taking the fast Fourier transform of the wideband response of the scene, at several external transmit/receive locations, produces 2D images of the clutter, which are used to mature the model.